双圆弧弧齿锥齿轮重合度研究 - 张瑞亮; 树学锋; 王铁; 武志斐 (Jixie chuandong)
The contact ratio is main effective factor on mesh characteristic of double circular arc profile spiral bevel gear（DCAPSBG）.The overlap contact ratio of DCAPSBG ensures its continuous transmission.Based on the contact ratio definition of spiral bevel gears,the contact ratio definition of DCAPSBG is proposed,and the meshing process is analyzed by using line-graph method.The calculation methods of the contact ratio,multi-points meshing coefficient and multi-pairs contact coefficient are established.The continuous transmission conditions of DCAPSBG are also provided.The contact ratio of testing gear is calculated by using the method.The calculation result is identical to that of tooth contact analysis（TCA）,and the correctness of the method is verified.